Bycatch of crustacean and fish bottom trawl fisheries from southern Portugal (Algarve) - Costa, Maria Esmeralda (2008)
As part of two research projects for analysing bycatch and discards, we quantified catch composition, catch rates, bycatch and discard,, in two important commercial bottom trawl fisheries (crustacean and fish trawls) off the Southern coast of Portugal (Algarve). Stratified sampling by onboard observers took place from February 1999 to March 2001 and data were collected from 165 tows during 52 fishing trips. Commercial tat-get species included crustaceans: blue and red shrimp (Aristeus antennatus), deep-water rose shrimp (Parapenaeus longirostris), Norway lobster (Nepharops norvegicus); and fishes: scabreams (Diplodus spl). and Pagellus Spp.), horse Mackerels (Trachurus spp.) and European hake (Merluccius merluccius). The trawl fisheries are characterised by considerable amounts of bycatch: 59.5% and 80.4% of the overall total catch for crustacean and fish trawlers respectively. A total of 255 species were identified, which belonged to 15 classes of organisms ( 137 vertebrates, 112 invertebrates and algae). Crustacean trawlers had higher bycatch biodiversity. Bony fish (45.6% and 37.8%) followed by crustaceans (14.6% and 11.5%) were the dominant bycatch components of both crustacean and fish trawlers respectively. The influence of a number of factors (e.g. depth, fishing gear, tow duration and season) on bycatch and discards is discussed.